2018
DOI: 10.1002/jnr.24356
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of circRNAs and RNA binding proteins: An important part of circRNA maintenance and function

Abstract: The widespread expression of circular RNAs (circRNAs) is regarded as a feature of gene expression in highly diverged eukaryotes. Recent studies have shown that circRNAs can act as a miRNA sponge to repress miRNA function, participate in splicing of target genes, translate genes into protein and interact with RNA binding proteins (RBPs). RBPs are a broad class of proteins involved in gene transcription and translation, and interaction with RBPs is considered an important part of circRNA function, which can serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
285
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(311 citation statements)
references
References 62 publications
3
285
0
Order By: Relevance
“…4 Recently, accumulating evidence has indicated that circRNAs play a pivotal role in cancer progression by regulating gene expression at the levels of chromatin modification, transcriptional, and posttranscriptional regulation. [5][6][7] Several studies have found that dysfunction of various circRNAs is closely related to the proliferation, apoptosis, migration, invasion, and drug resistance of tumor cells. 5,[8][9][10] Therefore, circRNAs may represent potential biomarkers with diagnostic, prognostic, and therapeutic values in human carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, accumulating evidence has indicated that circRNAs play a pivotal role in cancer progression by regulating gene expression at the levels of chromatin modification, transcriptional, and posttranscriptional regulation. [5][6][7] Several studies have found that dysfunction of various circRNAs is closely related to the proliferation, apoptosis, migration, invasion, and drug resistance of tumor cells. 5,[8][9][10] Therefore, circRNAs may represent potential biomarkers with diagnostic, prognostic, and therapeutic values in human carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, circRNA is capable of physically interacting with RNA-binding protein to regulate gene expression. 25 Herein, we found that circ-CCND1 could directly bind to HuR to potentiate CCND1 mRNA stability. HuR is a well-known RNA-binding protein that prevents mRNA decay via targeting the uridylate-rich element (ARE, (A/U)UUU(A/U)) on the 3′-UTR.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, circRNA is capable of physically interacting with RNA‐binding protein to regulate gene expression . Herein, we found that circ‐CCND1 could directly bind to HuR to potentiate CCND1 mRNA stability.…”
Section: Discussionmentioning
confidence: 86%
“…RNA transcription, pre-mRNA splicing and polyadenylation as well as modification, stability, localization, and translation of RNA (reviewed in (13) ). Recent studies have shown that RBPs also affect all phases of the circRNA lifecycle (reviewed in (14) ). Some RBPs are involved in circRNA biogenesis as has been shown for Quaking (QKI) (15) , FUS (16) , HNRNPL (17) , RBM20 (18) , and Muscleblind (19) , which bind to specific intronic RBP motifs and promote formation of some circRNAs in certain biological settings.…”
Section: Introductionmentioning
confidence: 99%